Analysis of The Effect of Non-Cash Payments, Interest Rate, and The Amount of The Money Circulation on Inflation in Indonesia - Ananda Putri; Safuridar Safuridar; Suri Amilia; Asnidar Asnidar (Institute of Computer Science (IOCS), 2022)
This study aims to determine how the partial and simultaneous influence of non-cash payments, interest rates and the money supply on inflation in Indonesia. This research was carried out from January 2021 to June 2021. The type of research data is quantitative. The independent variables in this study are non-cash payments (X1), interest rates (X2), and the money supply (X3) while the dependent variable is inflation (Y) with the object of research in Indonesia. Sources of data were collected in the form of secondary data for the 2009-2019 time series obtained from Bank Indonesia and the Central Statistics Agency. The analytical method used is multiple linear regression and classical assumption test. The results of the study partially state that non-cash payments and the money supply do not affect inflation, while interest rates have a significant effect on inflation in Indonesia. Simultaneously non-cash payments, interest rates and the money supply have a significant effect on inflation in Indonesia. ScoreR square is 0.4670 or 46.70%, meaning that the variables of e-money, interest rates, and the money supply affect inflation in Indonesia by 46.70%, while the remaining 53.30% is influenced by other factors outside the study.